2004
DOI: 10.1159/000078103
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulates Growth Hormone Secretion via a Direct Pituitary Effect Combined with a Decreased Somatostatin Tone in a Median Eminence-Pituitary Perifusion Study

Abstract: The aim of this study was to examine the effect of recombinant human leptin on growth hormone (GH) secretion in perifused anterior pituitary slices from adult pigs. Anterior pituitary slices from sows were perifused and treated with recombinant human leptin (10 nM) and GH-releasing hormone (GHRH; 1 nM). In some experiments, pituitary slices were coincubated with stalk median eminence (SME). In a subset of the coincubation experiments, immunoneutralization of endogenous GHRH and somatostatin (SRIH) release was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
5
28
0
2
Order By: Relevance
“…On the contrary, the highest doses (6 ϫ 10 Ϫ9 M) used in the initial experiments for detecting a possible action of leptin belong to the pharmacological domain. It must be emphasized that, in works using the patch-clamp technique on hypothalamic slices, leptin is currently perfused at 10 Ϫ6 to 10 Ϫ11 M (30,36,38,40). Leptin receptors are abundant in the lower brain, and particularly in the dorsal vagal complex, which includes the STN (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the highest doses (6 ϫ 10 Ϫ9 M) used in the initial experiments for detecting a possible action of leptin belong to the pharmacological domain. It must be emphasized that, in works using the patch-clamp technique on hypothalamic slices, leptin is currently perfused at 10 Ϫ6 to 10 Ϫ11 M (30,36,38,40). Leptin receptors are abundant in the lower brain, and particularly in the dorsal vagal complex, which includes the STN (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this understimulated pituitary, when incubated in vitro, releases more TSH than control pituitaries, indicating that some in vivo inhibitory factor is acting on the offspring of NIC dams (e.g., somatostatin). In fact, it has been demonstrated that leptin inhibits somatostatin in hypothalamic cultures (Saleri et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Wywiera ona także wielokierunkowe działanie na funkcjonowanie ośrodkowego układu nerwowego, wpływając na nastrój, emocje i procesy poznawcze [11,12]. LEP działa modulująco na wydzielanie horonów przysadkowych, stymulując wydzielanie TRH, GnRH, GH, PRL oraz hamując sekrecję ACTH [12][13][14]. W układzie sercowo-naczyniowym LEP może działać kardioprotekcyjnie, zmniejsza rów-nież toksyczne działanie lipidów zgromadzonych poza tkanką tłuszczową, w tym również w myocardium [15,16].…”
Section: © Copyright By Pteidd 2015unclassified
“…Pomimo że leptyna moduluje wydzielanie hormonów przysadki, to jej prawidłowa czynność nie jest niezbędna do zachowania dobowego profilu wydzielania LEP [12][13][14]49].…”
Section: Dyskusjaunclassified